Integración de las TIC y TAC como estrategias didácticas para mejorar el proceso de enseñanza en los docentes que imparten la asignatura de contabilidad y costos de la Unidad Educativa Juan de Velasco de la ciudad de Riobamba año lectivo 2020-2021. - Ruiz Barahona, Doris Maricela (2021)
The study aims to identify the problem of technological tools on the teaching process of teachers in the field of Cost Accounting. It was conducted at “Unidad Educativa Juan de Velasco” a school located in Riobamba-Ecuador, where the lack of technological equipment TIC and Tac was a major issue. As a starting-point, the reports were provided by the tutors of the private and public companies in the province of Chimborazo where the students carried out their professional practices or also called internships; The assigned evaluations were presented in three areas such as cognitive, procedural and behavioral, in which 81% of students registered low grades in terms of their cognitive and behavioral abilities. Due to its characteristics, the research was defined as quasi-experimental, since the surveys were carried out before and after the updating and training of cost accounting teachers in the use of ICT and TAC technological tools; it is descriptive, since it was not limited to the traditional educational paradigm even though it still prevailed in the institution, explanatory because through the use of data collection instruments of the 15 teachers, 56 students and the evaluative evidences of the institutions where they carried out the practices (internships). It was possible to show the correlation between the performance of students and teachers due to the relationship between the dependent and independent variables. The findings revealed that the teaching style of teachers before the training of them on how to use and utilize ICT and CAT Technological tools in their classrooms was not very motivating and had little impact on the students. Among the main conclusions it can be highlighted that the use of technology in the teaching process has various advantages, such as boosting student learning and improving the quality of their education, the teacher's creativity and empowerment was acknowledged through the creation of technology-based learning tools and resources that allow them to improve their teaching methods and develop effective teaching techniques.